Reaching millennium development goal 4 - The Gambia - Jasseh, M; Webb, E; Jaffar, S; Howie, S; Townend, J; Smith, P; Greenwood, B; Corrah, T (2011)
Objective To describe how, through a DSS in a rural area of The Gambia, it has been possible to measure substantial reductions in child mortality rates and how we investigated whether the decline paralleled the registered fall in malaria incidence in the country. Methods Demographic surveillance data spanning 19.5years (1 April 1989-30 September 2008) from 42 villages around the town of Farafenni, The Gambia, were used to estimate childhood mortality rates for neonatal, infant, child (1-4years) and under-5 age groups. Data were presented in five a priori defined time periods, and annual rates per 1000 live births were derived from Kaplan-Meier survival probabilities. Results From 1989-1992 to 2004-2008, under-5 mortality declined by 56% (95% CI: 48-63%), from 165 (95% CI: 151-181) per 1000 live births to 74 (95% CI: 65-84) per 1000 live births. In 1- to 4-year-olds, mortality during the period 2004-2008 was 69% (95% CI: 60-76%) less than in 1989-1992. The corresponding mortality decline in infants was 39% (95% CI: 23-52%); in neonates, it was 38% (95% CI: 13-66%). The derived annual under-5 mortality rates declined from 159 per 1000 live births in 1990 to 45 per 1000 live births in 2008, thus implying an attainment of MDG4 seven years in advance of the target year of 2015. Conclusion Achieving MDG4 is possible in poor, rural areas of Africa through widespread deployment of relatively simple measures that improve child survival, such as immunisation and effective malaria control. © 2011 Blackwell Publishing Ltd.